Defect analysis in mission‐critical software systems: a detailed investigation. Issue 1 (26th December 2014) - Carrozza, Gabriella; Pietrantuono, Roberto; Russo, Stefano
Abstract The practice of defect analysis is recognized as an essential task for software process measurement, yet its effective application in the industrial development of large‐scale software systems raises several challenges. We report the results of a study conducted at SELEX ES – a large system integrator leader in the market of software‐intensive mission‐critical systems. The article describes the defect analysis approach that we tailored to evaluate the software development process with respect to the quality of produced software and its relation with the required effort. Three key phases of the process were addressed, regarding the software implementation, the testing phase and the prerelease defect fixing activity, over a set of six computer software configuration items developed from 2009 to 2012 for the naval and maritime domain product line. The analysis highlighted efficiency bottlenecks in each of the monitored phases, providing company engineers with insights about room for process improvement. The implemented approach, the observed phenomena and the inferred conclusions are of support to practitioners coping with systems, development models and industrial environments similar to the considered one. Copyright © 2014 John Wiley & Sons, Ltd.